Accompaniment Marketing Product MSMEs Use Digital Marketing - Silviana Batubara; Ade Maya Mei Shanty; Makhrani (Jurnal Transformasi Pendidikan Indonesia, 2024)
Technological developments in the present demand all over society to be ready to face it challenges of the times. One of the hit impact development is in the business world . The more fast current consumption public , so they need technology For fulfil need daily . Nowadays, a lot consumers who use it facility technology information , one of them is using the internet. The internet is growing quickly and become one​ source information that is easy to access . Current changing times bring shopping lifestyle​ public shifted from its nature conventional changed become Online transactions are one of them via social media. Devotion This community focuses on understanding and optimizing the marketing of MSMEs in Sialaman Village Sipirok South Tapanuli, the aim is to make residents more capable and optimize use digitalization in marketing their MSME results , considering role dogotal in the current era very significant in marketing MSME products in society . In this community service we use R&D approach, which the author tries Analyze carefully​ jump straight into the field to unravel it problems that exist in society then mapped and finalized​ problem the.us We hope that in this service the community and MSME actors in the village will participate Silaman South Tapanuli will be even wider with this Utilization of digital marketing to disseminate the products that their MSMEs provide both at regional and international levels national for the sake of its creation the creativity of these MSME actors.